Time to blood cultures positivity of microorganisms using a continuous-monitoring automated blood cultures system - Pajaree Krisanapan (2020)
© 2019 Krisanapan and Chaiwarith, published by Sciendo. Previous studies showed that clinically significant pathogens were detected within 3 days of incubation using a continuous monitoring automated blood culture instrument. To determine time to blood culture positivity (TTP) of microorganisms using a BD BACTEC™ FX. A cross-sectional study was conducted at Maharaj Nakorn Chiang Mai Hospital, Thailand from October to November 2014. One-hundred and eighty-one patients with 195 episodes of infection and 436 cultures were included in the analysis. Among 181 patients, 55.2% were male and the median age was 61 years (interquartile range (IQR) 50, 76). Of the 195 episodes of infections, the most common source was genitourinary tract (15.4%). Overall, the median TTP was 17 hours (IQR 11.5, 24.5), the shortest TTP was observed in Streptococcus agalactiae. Four-hundred and seventy-eight cultures (97.6%) and all (100%) were detected at 3 days and 5 days of incubation. Factors associated with TTP ≤24 hour were blood drawn from patients who had hematologic malignancy (odds ratio (OR) 9.6, 95% confidence interval (CI) 1.2, 74.3, P = 0.030), endocarditis and vascular infection (OR 8.7, 95% CI 1.1, 67.2, P = 0.038), thrombocytopenia (OR 2.4, 95% CI 1.3, 4.4, P = 0.004), clinical of systemic inflammatory response syndrome (SIRS) (OR 2.3, 95% CI 1.2, 4.5, P = 0.014), and not receiving antimicrobials within 72 hours before cultures taken (OR 2.2, 95% CI 1.4, 3.6, P < 0.001). TTP varied depends upon the pathogens and clinical settings. However, bacteria were isolated from almost, but not all of the blood cultures within 3 days of incubation.